2009
DOI: 10.1002/pits.20371
|View full text |Cite
|
Sign up to set email alerts
|

Preventing boys' problems in schools through psychoeducational programming: A call to action

Abstract: Controversy currently exists on whether boys are in crises and, if so, what to do about it. Research is reviewed that indicates that boys have problems that affect their emotional and interpersonal functioning. Psychoeducational and preventive programs for boys are recommended as a call to action in schools. Thematic areas for boys' programming are enumerated including life skills and issues with masculinity ideology and gender role conflict. An example of a program that promotes positive and affirmative mascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The professional counseling discourse on men's developmental needs has evolved to include a strengths‐based framework that affirms diverse presentations of masculinity and explores it as a source of strength and resiliency (Englar‐Carlson & Kiselica, ; Kimmel, ; Kiselica, ; Levant & Pollack, ; O'Neil, ). This strengths‐based framework aligns with the counseling profession's general orientation (i.e., wellness model, developmental perspective, focus on prevention and early intervention, client empowerment; Remley & Herlihy, ) and has implications for the ways counselors intervene as helpers for male clients (Englar‐Carlson & Kiselica, ; Kimmel, ; O'Neil, ; O'Neil & Luján, ). Scholarship addressing effective interventions with men, specifically Black men, has frequently been formulaic and deficit focused, void of a discussion that focuses on the ways race and racialization influence this population's existence.…”
Section: Counseling Considerations For Menmentioning
confidence: 99%
“…The professional counseling discourse on men's developmental needs has evolved to include a strengths‐based framework that affirms diverse presentations of masculinity and explores it as a source of strength and resiliency (Englar‐Carlson & Kiselica, ; Kimmel, ; Kiselica, ; Levant & Pollack, ; O'Neil, ). This strengths‐based framework aligns with the counseling profession's general orientation (i.e., wellness model, developmental perspective, focus on prevention and early intervention, client empowerment; Remley & Herlihy, ) and has implications for the ways counselors intervene as helpers for male clients (Englar‐Carlson & Kiselica, ; Kimmel, ; O'Neil, ; O'Neil & Luján, ). Scholarship addressing effective interventions with men, specifically Black men, has frequently been formulaic and deficit focused, void of a discussion that focuses on the ways race and racialization influence this population's existence.…”
Section: Counseling Considerations For Menmentioning
confidence: 99%
“…To date, the bulk of the extant literature on the psychology of boys, men, and masculinity has been primarily focused on the important challenges of (a) creating an awareness about the detrimental effects of constricted forms of masculinity on boys and men and their relationships with others and (b) developing remedial approaches to counseling that are designed to help boys and men recover from dysfunctional masculinity (Kiselica, 2006, 2011; Kiselica & Englar‐Carlson, 2010; Kiselica, Englar‐Carlson, Horne & Fisher, 2008; O'Neil & Lujan, 2009). Kiselica (2011) and O'Neil and Lujan (2009) observed that the new psychology of men, although impressive and certainly beneficial, was overly focused on male pathology and identifying men's problems; it neglected any discussion of male strengths, adaptive behavior, and positive aspects of being a man. Isacco, Talovic, Chromik, and Yallum (2012) added, on the basis of the entirety of this research, that it is easy to take an essentialist perspective and conclude that traditional masculinity, or masculinity as a whole, is always negative.…”
Section: The Rationale For Using Strength‐based Approaches With Male mentioning
confidence: 99%
“…A new direction for the psychology of men is to create positive paradigms of healthy masculinity. Future research and conceptualization are needed on affirmative and positive aspects of masculinity (O'Neil, 2008, 2012; O'Neil & Lujan, 2009b). Patterns of positive masculinity can help men and boys learn alternatives to sexist attitudes and behaviors that cause GRC.…”
Section: Some Final Thoughts and New Directionsmentioning
confidence: 99%